The Relationship Between The Effectiveness Of Using Whatsapp And Changes In Behavior Of Horticulture Farmers In Negeri Tawiri, Teluk Ambon District - Helen Helen; Risyart. A. Far Far; Paul Melkianus Puttileihalat (International Journal of Economics, Business and Innovation Research, 2023)
Study This aim For to determine the effectiveness of receiving agricultural information through WhatsApp social media in increasing the knowledge of horticultural farmers in Negeri Tawiri, Teluk Ambon District. And to analyze the relationship between the effectiveness of whatsapp users and changes in the behavior of horticultural farmers. This research was conducted in Negeri Tawiri, Ambon Bay District. From November to December 2022. Samples were taken using a purposive sampling technique by determining the sample, the head of the farmer group, the secretary of the farmer group and 2 group members, so that a sample of 32 people/farmers was obtained. Data analysis used in this study was quantitative analysis using the Spearman Rank statistical test tool to see the relationship between the effectiveness of using WhatsApp and changes in farmer behavior. The results showed that the frequency, duration and attention to use of WhatsApp media among farmers were in the medium category. The majority of farmers use whatsapp 3-4 times/week while the duration of using whatsapp is 1-2 hours/day. And then pay attention to using whatsapp 3-4 times/week. This means that farmers often use whatsapp. And the results of the analysis using the Spearman rank test, there is no relationship between the effectiveness of using WhatsApp and farmer behavior. This is because farmers using WhatsApp are not fully used to seek, receive and disseminate agricultural information (horticultural crops). But whatsapp is also used as a medium of entertainment.